Recombinant Human Erythropoietin: Manfaat dalam Bidang Kedokteran - Yanuartono Yanuartono; Hary Purnamaningsih; Alfarisa Nururrozi; Soedarmanto Indarjulianto; Slamet Raharjo (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2019)
Recombinant human erythropoietin (rhEPO) is one of the biotechnology-based drugs that are needed by the human medicine and has also been used in the veterinary medicine. Currently RhEPO has been widely used in the world of human medicine for the treatment of anaemia caused by renal failure, cancer, chronic inflammation and AIDS. In veterinary medicine, although there is still not much data on its achievements, rhEPO has also been used for cases of chronic renal failure in dogs and cats. However, since rhEPO is not identical to feline EPO and canine EPO, some patients eventually produce antibodies against the drug. The antibodies not only prevent EPO therapy from being effective, but also may lead to severe and life-threatening anemia. This paper provides a review of the use of RhEPO, rfEPO and rcEPO in veterinary medicine, especially for the purpose of non-regenerative anemia therapy in cases of chronic renal failure in dogs and cats.